Active Carbon Respiratory Masks as the Adsorbent of Toxic Gases in Ambient Air. (2nd June 2019) - Khayan, Khayan; Anwar, Taufik; Wardoyo, Slamet; Lakshmi Puspita, Widyana
Abstract : The air quality that is increasingly carrying out pollution as a result of pollution by human activities is of concern to the world, both developed and developing countries. The impact of air pollution is unavoidable, especially for health. Several efforts have been made to suppress the occurrence of pollution starting from the control of sources, media, and protective efforts in human beings. Focusing on protective efforts, this study was carried out by designed respiratory masks capable of adsorbing toxic gases in ambient air by utilizing mask materials on the market with the addition of activated carbon; the study was carried out with an experimental approach. Testing distinguishes the ability of cotton, spunbond, meltblown, and activated carbon as a respiratory mask to absorb toxic gases such as COx, NOx, and SOx. Test statistics are using the ANOVA test with a confidence level of 95%, α = 5%. The results show that combining activated carbon, spunbond, and meltblown is more effective compared to respiratory masks made from spunbond and meltblown (surgical masks) in absorbing toxic gases.